John Kerr for Governor General [John Button, Bill Hayden, Bob Hawke] - Pryor, Geoff, 1944- (1981)
The Opposition is threatening to block some of the Fraser Government's Budget measures in the Senate, especially its attempt to extend sales tax by 2.5%, perhaps raising the spectre of former Governor General Sir John Kerr, and the infamous blocking of Supply in 1975.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 26 August 1981.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Hawke, Bob, -- 1929-2019 -- Caricatures and cartoons; Hayden, Bill -- 1933- -- Caricatures and cartoons; Button, John, -- 1933-2008 -- Caricatures and cartoons; Kerr, John, -- Sir, -- 1914-1991 -- Caricatures and cartoons; Australian Labor Party -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons